UJI TOOLS PADA METODE APPLIED BEHAVIORAL ANALYSIS DALAM MENDIDIK AUTIS MENGHADAPI MENARCHE - Prastiwi, Ratih Sakti; Hastuti, Sari; Sumarah, Sumarah (Jurnal Kesehatan Ibu dan Anak, 2013)
The developing preteen autism have the same development as the normal ones. Autism uneducated sexual have risked get sexual harassment ABA method are commonly used for therapies, study showed 47.0% autism will have normal behavioral. Result of former study showed that autism spent more time to have activities at schools and have more interaction with their teachers. Purpose of the research: to make tools such as small pictured books and the lesson plan for applied behavioral analysis method in preparing autism facing menarche. Method of this research are action research and descriptive survey. The sample of this research using snowballing technic. This research takes 15 respondents. Analysis technic uses content analysis and item analysis using Pearson product moment. Result: The result of this research are the books of small pictured books can be used as prompt for preparing autism facing menarche. Descriptive analysis showed expedience degree of appropriate are 66.7% and for the content are 87.1%. Tools of lesson plan has the component and material accordance with Permendiknas No. 41 tahun 2007. The result of item analysis shows that item which can be used are: identity, standard competency, learning indicator, learning material, learning resource, the material is understandable and systematic. Expedience degree of lesson plan are 85.5% and far reference lessons are 80.0%o. Conclusion: lesson plan and pictures books as tools can be used